ORPHANS AND CHILDREN DEPRIVED OF PARENTAL CARE STUDY AT SCHOOL PROBLEMS IN OBTAINING A QUALITY EDUCATION AND UPBRINGING (Neo Scientific Peer Reviewed Journal, 2023)
This article expresses opinions on the problems of teaching and educating orphans and children deprived of parental care in schools.